Effect of Heat Treatment on Microstructure, Acidic Corrosion Resistance and Wear Performance of Low-Carbon Steel - Aramide, Basiru Philip; Jamiru, Tamba; Adegbola, Taoreed; Popoola, Abimbola Patricia Idowu (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Low-carbon steels are widely used in structural and industrial applications, but their performance can be significantly enhanced through controlled thermal processing. This paper looks at how different heat treatment techniques affect low-carbon steel's microstructure, corrosion resistance in acidic settings, and wear performance. Mechanical and electrochemical behaviours were evaluated under four heat treatment conditions: normalizing (A), water quenching (Q), normalizing followed by quenching (AQ), and double (cyclic) quenching (QQ). Phase changes were characterized by optical microscopy; Vickers microhardness testing and depth profiling evaluated hardness distribution. Using linear polarization techniques, electrochemical corrosion tests in dilute sulfuric acid (H₂SO₄) were run to find corrosion potential, current density, and polarization resistance. Using a pin-on-disc apparatus, wear performance was also assessed under 10 N and 20 N loads. Results revealed that quenching greatly increased surface hardness because of martensite formation; Q had the highest microhardness but lower corrosion resistance because of microstructural stress and heterogeneity. By contrast, AQ offered a balanced microstructure with fair hardness and excellent corrosion resistance. Wear rates were closely connected to hardness; QQ showed the greatest wear resistance at both load conditions. These results highlight the importance of heat treatment in maximizing the surface integrity of carbon steel for uses in mechanically hostile and acidic environments.